Which Treatment is More Effective for Functional Ankle Instability: Strengthening or Combined Muscle Strengthening and Proprioceptive Exercises? - Kim, Ki-Jong; Kim, Young-Ok; Kim, Young-Eok; Lee, Jin-Su; Seo, Tae-Hwa; Ji, Sung-Ha; Ji, Sang-Goo; Jun, Hyun-Ju (Journal of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to implement combined muscle strengthening and proprioceptive exercises to examine the effects of combined exercises on functional ankle instability. [Subjects and Methods] Experiments were conducted with 30 adult males and females. The study subjects were randomly assigned to either a control group (Group A), a muscle strengthening exercise group (Group B), or a combined muscle strengthening and proprioceptive exercise group (Group C) consisting of 10 subjects each. In Group A, measurements were only conducted before and after the experiment without any intervention, whereas the exercise programs for Group B and Group C were implemented three days per week for four weeks. [Results] Muscle strength showed significant increases in Groups B and C compared with the control group during plantar flexion, dorsiflexion, inversion, and eversion. The Cumberland ankle instability tool showed significant increases in Group B and Group C compared with Group A and significant increases in Group C compared with Group B. [Conclusion] Applying combined muscle strengthening and proprioceptive exercises to those who have functional ankle instability is more effective than applying only muscle strengthening exercises.